2010
DOI: 10.2134/jeq2009.0323
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Catchment Vulnerability to Diffuse Herbicide Losses from Hydrograph Statistics

Abstract: The prediction of diffuse herbicide losses to surface waters using process-based models is data and time demanding. There is a need for simpler and more efficient catchment screening tools. We developed and tested a new proxy for screening catchments for their vulnerability to diffuse herbicide losses relying on widely available river flow data only. The proxy combines the fast flow index (FFI) (i.e., the long-term average proportion of fast flow to total discharge) and the fast flow volume (FFVs) (i.e., the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
(63 reference statements)
0
15
3
Order By: Relevance
“…The observation that findings from small catchments can be extrapolated to larger areas in a meaningful manner may be considered a contradiction to earlier work where important spatial differences between herbicide loss rates within catchments were demonstrated (Doppler et al, 2014;Leu et al, 2010). However, the data suggest that spatial heterogeneity at small scales is averaged out at larger ones such that it does not dominate the large scale patterns.…”
Section: Model Performancecontrasting
confidence: 65%
See 1 more Smart Citation
“…The observation that findings from small catchments can be extrapolated to larger areas in a meaningful manner may be considered a contradiction to earlier work where important spatial differences between herbicide loss rates within catchments were demonstrated (Doppler et al, 2014;Leu et al, 2010). However, the data suggest that spatial heterogeneity at small scales is averaged out at larger ones such that it does not dominate the large scale patterns.…”
Section: Model Performancecontrasting
confidence: 65%
“…The concept to describe the transfer of the applied herbicides from the fields to the river is based on the empirical observation that herbicide concentrations increase with flow during discharge events during the application period (Leu et al, 2010). Mechanistically this can be explained by the occurrence of fast transport processes (with high herbicide concentrations) such as surface runoff and fast subsurface flow through drainage systems or macropores (Leu et al, 2004a) during discharge events.…”
Section: Outputmentioning
confidence: 99%
“…This shows that a different runoff regime was active during event E13. Our observation that infiltration excess overland flow is the main transport process for herbicides is in contrast to previous studies in the Swiss Plateau (Leu et al, 2004a(Leu et al, , 2010Gomides Freitas et al, 2008), which indicated that saturation excess overland flow was the dominant process controlling diffuse herbicide pollution.…”
Section: Transport Processes and Csascontrasting
confidence: 99%
“…Pesticides can enter the water system, where they can harm aquatic organisms even in low concentrations. Small streams in catchments with intensive crop production are especially at risk (Liess and Schulz, 1999), as diffuse pollution from agricultural fields causes major inputs to the stream in these areas (Leu et al, 2010). Pesticides mainly enter surface waters during rain events, when they are mobilised and transported with fast runoff (Thurman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides can enter the water system, where they can harm aquatic organisms even in low concentrations. Small streams in catchments with intensive crop production are especially at risk (Liess and Schulz, 1999), as diffuse pollution from T. Doppler et al: Spatial variability of herbicide mobilisation and transport agricultural fields causes major inputs to the stream in these areas (Leu et al, 2010). Pesticides mainly enter surface waters during rain events, when they are mobilised and transported with fast runoff (Thurman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%